The Space of Culture - the Place of Nature in Estonia and Beyond - Peil, Tiina (Approaches to Culture Theory, 2011)
This volume sets out to construct a tentative bridge between the physical and perceived (academic) worlds, between the understandings of culture and nature, their spatiality and temporality by tackling the spatiality of culture phenomena across disciplinary boundaries. The contributions are arranged around a general question of how humans organise the spaces in which they live. The book is divided according to three themes: the humanities and ecosemiotic approach to nature, constructing nature, and examining environmental and landscape change. The first provides an historical review of the humanities and expands on the more theoretical themes. The second section discusses some ways in constructing (wild) nature with specific examples. The final one illustrates the changes that various cultures have brought about in the environment examining landscapes and domestication. The space of culture and the place of nature in various cultures are discussed critically throughout the volume in a way that challenges their ontological separations and invites to discuss culture-nature relationships on a more balanced basis.